2011
DOI: 10.1111/j.1439-0434.2010.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Markers Reveal Genetic Variation within Sclerotinia sclerotiorum Populations in Irrigated Dry Bean Crops in Brazil

Abstract: Eriston riston Vieira ieira Gomes omes 1 , Lucas ucas Breseguello reseguello do do Nascimento ascimento 1 , Marcos arcos Augusto ugusto de de Freitas reitas 2 , Luiz uiz Carlos arlos Bhering hering Nasser asser 2 and Silvana ilvana Petrofeza etrofeza 1 AbstractMicrosatellites are powerful markers to infer population genetic parameters. We used 10 microsatellite loci to characterize the genetic diversity and structure of 79 samples of Sclerotinia sclerotiorum isolated from four Brazilian dry bean populations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 42 publications
2
33
1
5
Order By: Relevance
“…Sound breeding programs require proper understanding of the pathogen variability. The variability of populations of S. sclerotiorum has been investigated for different crops around the world and most studies have focused on polymorphisms of neutral molecular markers (Cubeta et al, 1997;Sexton et al, 2004;Sexton et al, 2006;Malvárez et al, 2007;Ekins et al, 2011;Gomes et al, 2011;Clarkson et al, 2013).Phenotypic variability has been observed among isolates of S. sclerotiorum collected from different hosts in Canada (Morral et al, 1972), rape in Turkey (Merk-Turk et al, 2007) and Australia (Garg et al, 2010) and canola in China and USA (Attanayake et al, 2013). On the other hand, phenotypic uniformity was observed among isolates from potato in USA (Atallah et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sound breeding programs require proper understanding of the pathogen variability. The variability of populations of S. sclerotiorum has been investigated for different crops around the world and most studies have focused on polymorphisms of neutral molecular markers (Cubeta et al, 1997;Sexton et al, 2004;Sexton et al, 2006;Malvárez et al, 2007;Ekins et al, 2011;Gomes et al, 2011;Clarkson et al, 2013).Phenotypic variability has been observed among isolates of S. sclerotiorum collected from different hosts in Canada (Morral et al, 1972), rape in Turkey (Merk-Turk et al, 2007) and Australia (Garg et al, 2010) and canola in China and USA (Attanayake et al, 2013). On the other hand, phenotypic uniformity was observed among isolates from potato in USA (Atallah et al, 2004).…”
mentioning
confidence: 99%
“…Sound breeding programs require proper understanding of the pathogen variability. The variability of populations of S. sclerotiorum has been investigated for different crops around the world and most studies have focused on polymorphisms of neutral molecular markers (Cubeta et al, 1997;Sexton et al, 2004;Sexton et al, 2006;Malvárez et al, 2007;Ekins et al, 2011;Gomes et al, 2011;Clarkson et al, 2013).…”
mentioning
confidence: 99%
“…If the population is recombining or presents genetic exchange, markers, MCG, and fingerprint will not be associated. This has been observed in subtropical populations of S. sclerotiorum (Cubeta et al, 1997;Carbone and Kohn, 2001b;Meinhardt et al, 2002;Atallah et al, 2004;Sexton et al, 2006;Gomes et al, 2011;Litholdo Júnior et al, 2011). In a highly recombinant population, the expectation is that each isolate sampled, or most of them, is either incompatible with all other isolates or is part of an intransitive MCG, and each isolate either has a unique fingerprint or a fingerprint associated with more than one MCG.…”
Section: Recombination Vs Clonal Reproductionmentioning
confidence: 67%
“…Isolates taken from beans and two other crops from another region of Brazil showed the same two MCGs and had identical banding patterns for the telomere and microsatellite primers (Meinhardt et al, 2002). In a subsequent work, Gomes et al (2011) analyzed 79 isolates of S. sclerotiorum collected from four common bean center-pivot-irrigated fields and using microsatellite markers observed high genetic diversity within and among populations. The authors suggested that the occurrence of exclusive alleles in the populations analyzed may indicate the introduction of new genotypes in these areas at different moments through contaminated seeds or agricultural implements, in addition to the occurrence of sexual outcrossing and clonal reproduction.…”
Section: Sclerotinia Sclerotiorum Populations In South Americamentioning
confidence: 91%
See 1 more Smart Citation